Kompensasi Lingkungan Kerja dan Motivasi Terhadap Kinerja Pegawai PT Angkasa Pura 1 di Bandar Udara Adi Soemarmo - Risma Nur Pratiwi; Esti Dwi Rahmawati; Agus Suyatno (Universitas 45 Surabaya, 2024)
Study This aim For analyze role mediation motivation work on influence compensation and environment Work to performance employee of PT Angkasa Pura 1 Adi Soemarmo Airport Branch Office . Population in study This is employee employees of PT Angkasa Pura 1 Adi Soemarmo Airport Branch Office who work more of 1 ( one ) year and amount sample in study This as many as 87 respondents . Variables used​ in study This is compensation , environment work , motivation work and performance employee . Data used in study This in the form of primary data. Data collection methods used is questionnaire . Data analysis techniques used is Structural Equation Modeling -Partial Least Square (SEM-PLS) and using the SmartPLS 4.0 program . Research result This show that compensation influential positive and significant to motivation work , environment Work influential positive and significant to motivation work , compensation influential positive and significant to performance employees , environment Work influential positive and significant to motivation work , motivation Work influential positive and significant to performance employees , compensation influential positive and significant to performance employee through motivation Work as intervening variables , as well environment Work influential positive and significant to performance employee No through motivation Work as intervening variable .